Efeito da calcinação da magnésia precipitada sobre o processamento de cimentos de fosfato de magnésio - Paula, Gustavo Rocha de (2004)
It is great the interest for materials synthesized at room temperature because they represent an alternative for the current problems of energy. The class of magnesia phosphate cements belongs to this group, being mouldable ceramics that combine low density and good mechanical strength in a short period of time. The main disadvantage of these materials resides in their cost, even high if compared to Portland cement. The calcination stage of the magnesium oxide (MgO), necessary due to the high reactivity of that oxide with phosphates, is especially costly, besides the need of the addition of retardants to increase the setting time of these cements. The present work aimed to study forms of increasing the setting time of these cements and to evaluate alternatives to decrease the calcination temperature of MgO powders. Techniques such as X ray diffraction, infrared spectroscopy, scanning electronic microscopy, Hg porosimetry, He picnometry, and analyses of particle size distribution, specific surface area, apparent density and compression strength were used for the characterization of the calcined MgO powders and the cements. In a scientific-technological point of view, the main contribution of this work was the use of both liquid phase former additives and the microwave radiation for the calcination of MgO. In these conditions powders with appropriate particle size distributions and low specific surface areas were produced, which led to cements with longer reaction time and high mechanical strength. The microwave assisted calcination of MgO powders at 900 oC, with microwave absorbing raw materials, resulted in cements with superior properties when compared to those ones produced with powders calcined in conventional furnaces at 1100 oC. Another advantage was a heating rate five times faster and the temperature dwell four times shorter than those ones used in conventional firing. Such facts demonstrate the promising use of additives and the microwave firing to decrease the temperature of calcination of MgO and optimize the properties of magnesia phosphate cements.